Solid state insurrection : how the science of substance made American physics matter - Martin, Joseph D. (University of Pittsburgh Press, 2018)
Solid state physics--the study of the physical properties of solid matter--was far and away the most populous subfield of Cold War American physics. But despite prolific contributions to consumer and medical technology, such as the transistor and magnetic resonance imaging, it garnered much less professional prestige and public attention than nuclear and particle physics. Solid State Insurrection argues that solid state physics was nonetheless essential to securing the vast social, political, and financial capital Cold War physics enjoyed. Solid state's technological bent, and its challenge to the "pure science" ideal many physicists cherished, helped physics as a whole respond more readily to Cold War social, political, and economic pressures. Solid state research kept physics economically and technologically relevant, sustaining its lofty cultural standing and policy influence long after the sheen of the Manhattan Project had faded. By placing solid state at the center of the story of twentieth century science, this book brings a new perspective to some of the most enduring questions about the role of physics in American history